2021
DOI: 10.1017/xps.2021.17
|View full text |Cite
|
Sign up to set email alerts
|

The Generalizability of Online Experiments Conducted During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic imposed new constraints on empirical research, and online data collection by social scientists increased. Generalizing from experiments conducted during this period of persistent crisis may be challenging due to changes in how participants respond to treatments or the composition of online samples. We investigate the generalizability of COVID era survey experiments with 33 replications of 12 pre-pandemic designs, fielded across 13 quota samples of Americans between March and July 2020. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 42 publications
2
70
0
1
Order By: Relevance
“…While it is encouraging that attitudes on key variables of interest in our survey comport well with probability surveys conducted around the same time, making descriptive inferences about the U.S. adult population from quota samples is generally inadvisable because they may still differ from the target population on unobserved characteristics. 8 However, a large body of prior work has demonstrated that survey experimental estimates obtained from nonprobability samples (including undergraduates and Amazon Mechanical Turk workers) closely match those from probability samples, demonstrating that results from nonprobability samples typically generalize to the broader population (Berinsky et al, 2012;Coppock, 2019;Coppock et al, 2018;Coppock & McClellan, 2019;Mullinix et al, 2015;Peyton et al, 2021). Our primary focus in this paper is therefore on the inferences that can be made from the survey experimental estimates we obtain.…”
Section: Data and Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…While it is encouraging that attitudes on key variables of interest in our survey comport well with probability surveys conducted around the same time, making descriptive inferences about the U.S. adult population from quota samples is generally inadvisable because they may still differ from the target population on unobserved characteristics. 8 However, a large body of prior work has demonstrated that survey experimental estimates obtained from nonprobability samples (including undergraduates and Amazon Mechanical Turk workers) closely match those from probability samples, demonstrating that results from nonprobability samples typically generalize to the broader population (Berinsky et al, 2012;Coppock, 2019;Coppock et al, 2018;Coppock & McClellan, 2019;Mullinix et al, 2015;Peyton et al, 2021). Our primary focus in this paper is therefore on the inferences that can be made from the survey experimental estimates we obtain.…”
Section: Data and Resultsmentioning
confidence: 89%
“…Following best practices to ensure data quality in online research, we restricted participation to respondents who read and passed an attention screener placed at the beginning of the survey (see Aronow et al, 2020;Peyton et al, 2021 for recent work on respondent attentiveness, and Online Appendix Sections C.1 and D.1 for additional details). Of the 2099 respondents who consented to participate in the survey, 1137 passed the attention check and completed the survey.…”
Section: Data and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Questions about the data produced during the COVID-era, whether it is reliable and generalizable due to the extraordinary circumstances, emerged during the height of the pandemic. In response, Peyton et al (2020) replicated data from multiple online studies to analyze whether people's political preferences could have shifted and if the pandemic changed the types of respondents. Their results show that there could be an increase in "inattentive survey subjects (Peyton et al, 2020, 16)."…”
Section: Survey Recruitmentmentioning
confidence: 99%
“…Lucid is an increasingly popular alternative to Amazon Mechanical Turk for social science survey research. Many well-known findings have been replicated on Lucid, suggesting the platform is capable of providing high-quality data (Coppock and McClellan 2019;Peyton, Huber, and Coppock 2021). During the COVID-19 pandemic, Ternovski and Orr (2022) found that Lucid data can provide reliable data when researchers screen on attentiveness, which we do here.…”
Section: Study 1: Fictional Politicianmentioning
confidence: 52%